2017
DOI: 10.1088/2040-8986/aa74d4
|View full text |Cite
|
Sign up to set email alerts
|

Metamaterials at the University of Southampton and beyond

Abstract: At the University of Southampton, research on metamaterials started in 2000 with a paper describing a metallic microstructure, comprising an ensemble of fully metallic 'molecules'. In the years since then, metamaterials have evolved from an approach for designing unusual electromagnetic properties by structuring matter at the sub-wavelength scale to become a universal paradigm for active functional media with optical properties on demand at any given point in time and space. Metamaterials are now recognized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 160 publications
0
6
0
Order By: Relevance
“…A novel MTM unit-cell for satellite applications was proposed in [23]. The proposed MTM structure was developed on a 1.6mm thick FR-4 dielectric substrate with an overall dimension of 30×30mm 2 . For the parametric analysis and comparative study, different substrate materials such as lossy Polymide, Aluminum Nitride, and Rogers RT 6010 were utilized.…”
Section: Figure 1 Classification Of Metamaterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel MTM unit-cell for satellite applications was proposed in [23]. The proposed MTM structure was developed on a 1.6mm thick FR-4 dielectric substrate with an overall dimension of 30×30mm 2 . For the parametric analysis and comparative study, different substrate materials such as lossy Polymide, Aluminum Nitride, and Rogers RT 6010 were utilized.…”
Section: Figure 1 Classification Of Metamaterialsmentioning
confidence: 99%
“…In contrast to natural materials, the MTM interacts with both light and sound waves in unanticipated patterns. The MTM has the potential to control the propagation of light inside waveguides and in free space [2]. Therefore, the ability to influence the propagation of EM waves and the outstanding features of MTM made it appropriate for various applications such as antennas, satellite communication, optical filters, invisibility cloaking, shielding properties, biosensors, sensor detection, signal multiplexing, holography, data processing, and battlefield communication [3][4][5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a diversity of VO 2 -hybrid active metamaterials or metadevices emerged from the visible to THz and microwave range, e.g., tunable absorbers [ 83 ], THz modulators [ 81 , 99 ], THz switches [ 94 ], wavefront engineering [ 95 ] etc. In addition, a few review papers about VO 2 -hybrid active metamaterials had been reported [ 56 , 100 , 101 , 102 ]. However, due to the volatile nature of VO 2 , its metallic phase vanishes as long as the external stimuli are withdrawn.…”
Section: Origin Of Pcm For Active Photonicsmentioning
confidence: 99%
“…By a close inspection of tunable resonance/transmission peak of the G 2 S 2 T 5 -hybrid plasmonic crystal, the relationship between the fraction of crystallization and baking time is quantitatively explored, as shown in Figure 2 b. In addition, another type phase change chalcogenide in the PCM family, G 3 S 2 T 6 , with lower mid-IR loss, was also introduced into the active metasurfaces based on the plasmonic resonances of Al antenna array [ 56 , 112 ], shown in Figure 2 c,d. A femtosecond laser pulse (800 nm, 50 fs and repetition rate of 960 Hz) was also used to trigger the reversible amorphous–crystalline phase transition for optically tunable transmission [ 112 ].…”
Section: Active Amplitude Controlmentioning
confidence: 99%
See 1 more Smart Citation